2014
DOI: 10.1089/bfm.2013.0082
|View full text |Cite
|
Sign up to set email alerts
|

Employee Perception of Breastfeeding-Friendly Support and Benefits of Breastfeeding as a Predictor of Intention to Use Breast-Pumping Breaks After Returning to Work Among Employed Mothers

Abstract: Background: Although increasing numbers of large companies are complying with demands for a breastfeedingfriendly workplace by providing lactation rooms and breast-pumping breaks, the effectiveness for intention to use breast-pumping breaks to express breast milk among employed mothers is uncertain. To explore the impact of employees' perceived breastfeeding support from the workplace and the benefits of breastfeeding on a woman's intention to use breast-pumping breaks after returning to work, we conducted a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 27 publications
(35 reference statements)
4
29
0
11
Order By: Relevance
“…After returning to work, only 50.3% of respondents continued breastfeeding. This result is in line with the 49.8% that was found by Tsai () and the 49% at 12 weeks after birth that was determined by Dagher, McGovern, Schold, and Randall (), but our findings indicate a higher rate than the 40% found by Weber et al ().…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After returning to work, only 50.3% of respondents continued breastfeeding. This result is in line with the 49.8% that was found by Tsai () and the 49% at 12 weeks after birth that was determined by Dagher, McGovern, Schold, and Randall (), but our findings indicate a higher rate than the 40% found by Weber et al ().…”
Section: Discussionsupporting
confidence: 93%
“…The workplace environment was adequate for our participants, as shown by the scores. As other studies have indicated, social support in the workplace is important to breastfeeding maintenance (Dabritz et al, ; Tsai, , , ). Break time and coworker support were identified by women as positive elements.…”
Section: Discussionmentioning
confidence: 81%
“…One study found that low-income women who were employed in administrative and manual labor occupations were more likely to end breastfeeding than women working in service jobs and career professionals (Kimbro, 2006). Employer and coworker attitudes and safe, sanitary places for breastfeeding/ expressing milk affect the extent to which mothers successfully combine work and breastfeeding (Bai and Wunderlich, 2013;Tsai, 2014a). Paid maternity and family leave are also associated with better breastfeeding outcomes (Baker and Milligan, 2008;Shepherd-Banigan and Bell, 2014).…”
Section: Respondent (N)mentioning
confidence: 99%
“…However, companies do not have obligations to provide breast pump device. Workers should bring the pump by themselves [ 57 ]. Hong Kong also supports workers to continue breastfeeding after returning to work.…”
Section: Breastfeeding Policy and Support For Female Workers Among Comentioning
confidence: 99%